Audit expectation gap: An empirical analysis - Paul Olojede; Olayinka Adedayo Erin; Osariemen Asiriuwa; Momoh Usman (Future Business Journal, 2020)
The financial debacles that occurred in the companies like Enron, WorldCom, and Xerox in the USA, Lehman Brothers, Polly Peck in the UK and African Petroleum Plc., Cadbury Plc., in Nigeria had created public distrust with the auditors. The era when the auditor will say "trust me" and that being accepted is over. Now, they must earn the public trust. This study provides an empirical analysis of the scope and nature of audit expectation gap in Nigeria. We used a descriptive and survey research design to achieve the objective of the study. We also collected data through primary source, using structured questionnaire. The study used Mann-Whitney U test and Kolmogorov-Smirnov Z test for the analysis of data and test of normality of distribution, respectively. The results confirmed that audit expectation gap exists in Nigeria, and the new auditor's report did not have any serious impact in reducing the gap. From the outcome of this study, the audit expectation gap primarily arose from the unreasonable expectation of the users due to their lack of understanding of the roles of auditors. We recommend the launching of a new business-reporting model geared towards releasing more non-financial information to the public and with clear description of the role of independent audit.
Keywords: 650; Audit expectation gap; Audit failure; Corporate failure; New auditors report; Role conflict theory